Predictive maintenance of a worm reducer with an unbalanced load - Goncalves, Aparecido Carlos [UNESP]; Paschoalini, Amarildo Tabone [UNESP]; Bazani, Marcio Antonio [UNESP] (Inderscience Enterprises Ltd, 2014)
Among all predictive maintenance techniques the oil analysis and vibration analysis are the most important for monitoring some mechanical systems. The integration of these techniques has potential to improve industrial maintenance practices and provide a better economic gain for industries. To study the integration of these two techniques, a test rig was set up to obtain an extreme working condition for the worm reducer used in this paper. The test rig was composed by a motor connected to a reducer through a flexible coupling and with an unbalanced load. The analysis of the results carried out by using a sample of the oil recommended by the manufacturer in extreme conditions, and using liquid contaminant is presented. From the results it was observed that if there is an abnormal instantaneous load in a system, the subsequent vibration analysis may not perceive what occurred if there was no permanent damage, which is not the case with the lubricant analysis.
Keywords: predictive maintenance; oil analysis; vibration analysis; tribology; wear